Hubungan Pola Komunikasi terhadap Atlet Esports Mobile Legend - Alfarisi, Salman; Rakhman, Arie; Rahmadi, Rahmadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between communication patterns and self-confidence in esports athletes on the Mobile Legends team. Data collection uses a quantitative approach with a relationship or correlation type of research method, a descriptive survey method with a sampling technique selected by purposive sampling with categories of 4 teams that consistently participate in competitions, which always experience defeat and victory in every competition in Banjarbaru City. From several analyses then, the result is the relationship between communication patterns and self-confidence in Mobile Legends esports athletes, which is related to the communication pattern that a Mobile Legends esports athlete needs to be more confident, namely a multi-directional communication pattern where all players can communicate thoroughly when inside competitions, evaluations, even when giving ideas to each other. The conclusion of the research regarding the relationship between communication patterns and self-confidence in MLBB esports athletes in Banjarbaru City is that they have good communication so that a team of athletes has strong self-confidence for a team that always wins, in contrast to a team that often experiences defeat, they always miscommunication occurs so that mistakes frequently occur in matches, therefore good communication will make athletes themselves have high self-confidence in a team and will create calm in the game. Keywords: communication patterns, Esports Mobile Legend